(untitled) (Simbiótica. Revista Eletrônica, 2022)
This essay, composed of four independent acts but intersected from the idea of an overvaluation of the image - of a tensioned concept of hyperimage, aims to reflect on the dimensions of cultural consumption in the digital spheres and the problems that emerge from their polarizations, that is, the substantial, but continually obliterated, differences between real and virtual and their consequences on the bodies and subjectivities of individuals in contemporary times. Starting from a self-making ethnographic - which computes the consumption of the author on social media in the period of social isolation imposed by the pandemic of COVID-19 - and from an artistic writing practice, this work departs from any resolutive or axiomatic pretension for postulate itself as an open provocation, a way of reinserting debates about the subject in digital realities and how these last interfere and torment real bodies and identities. Keywords: hyperimage; social media; pornographyzation of life.